Ideal period for mating females of the predator Podisus fuscescens (Dallas, 1851) (Hemiptera: Pentatomidae) - Moreira da Silva, Isabel; Mendes de Sá, Veríssimo Gibran; Rodrigues Porto Pedrosa, Aline; dos Santos Cabral, Maria Jéssica; Leão Demolin Leite, Germano; Soares, Marcus Alvarenga; Cola Zanuncio, José M. (Revista Colombiana de Entomología, 2022)
The improvement of techniques for the mass rearing of predators in the laboratory, including the age of mating is important to obtain the largest number of individuals for biological control programs. The purpose of this study was to evaluate the females’ fecundity of the predator Podisus fuscescens (Dallas, 1851) (Hemiptera: Pentatomidae) with different pre-mating periods. The females of this predator were mated immediately after emergence (T1) or with one (T2), two (T3), three (T4), four (T5) or five (T6) days after emergence. The females mated immediately and one day after the emergency (T1 and T2) had fewer egg clusters than those mated after five days (T6). The number of nymphs per female was lower for those mated immediately after the emergence (T1) and with one (T2) or two days (T3). The total number of eggs was lower in females mated one day after emergence (T2) than for those mated after five days (T6). The proportion of hatched eggs was lower in the treatments T1 and T2 than in the T6. The oviposition and longevity of P. fuscescens females were similar between treatments; however, the pre-oviposition period longer in the T1 than T5 and T6. The pos-oviposition period was longer in the T1. Podisus fuscescens females require five days after emergence to mature their reproductive system, which improves their fitness and avoids unnecessary mating.